2008
DOI: 10.1631/jzus.b0820034
|View full text |Cite
|
Sign up to set email alerts
|

OMOM capsule endoscopy in diagnosis of small bowel disease

Abstract: OMOM CE is a useful diagnostic tool for the diagnosis of variably suspected small bowel disease, whose diagnostic efficiency is similar to that of the Pillcam SB (small bowel) CE (Given Imaging, Yoqneam, Israel).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 21 publications
0
32
0
2
Order By: Relevance
“…There are additional SB capsule systems that are not currently available in Turkey. One is from China, the OMOM pill (Jinshan Science and Technology; Chongqing, China) and there is also a Korean model (MicroCam, Intromedic; Seoul, Korea) [68,69] . Both the capsule endoscopes are similar to the PillCam in terms of battery life, dimensions, field of view and picture intervals.…”
Section: Other Types Of Capsule Endoscopementioning
confidence: 99%
See 1 more Smart Citation
“…There are additional SB capsule systems that are not currently available in Turkey. One is from China, the OMOM pill (Jinshan Science and Technology; Chongqing, China) and there is also a Korean model (MicroCam, Intromedic; Seoul, Korea) [68,69] . Both the capsule endoscopes are similar to the PillCam in terms of battery life, dimensions, field of view and picture intervals.…”
Section: Other Types Of Capsule Endoscopementioning
confidence: 99%
“…The first trial of the OMOM CE revealed comparable results to the PillCam. The authors express the cost advantage over other CEs, which could affect the choice of CE systems because of reimbursement problems [69] . PillCam SB2 and EndoCapsule have real time viewer capability that may shorten the examination once the cecum is seen.…”
Section: Other Types Of Capsule Endoscopementioning
confidence: 99%
“…Both the lighting and the rate of image capture, up to 15 per second, can be adjusted with this capability, which is the first commercial demonstration of two-way transmission. In China, this capsule has been found to have similar diagnostic rates as the PillCam SB, but at half the cost [7].…”
Section: Historymentioning
confidence: 95%
“…Table 1 summarizes most of the capsule endoscopy advances done during the last years. Currently there are only a few commercial capsules [4][5][6][7][8]. At research level it is possible to find several capsules claiming outstanding performances in diagnosis [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%